Advancing perioperative care in breast oncology: The synergistic potential of electroacupuncture and nonsteroidal anti-inflammatory drugs analgesia - Lei Gao; Yan Liu; Tie-Jun Pan; Zhen-Yu Liu (World Journal of Clinical Oncology, 2026)
This editorial examines the case control study by He et al recently published in World Journal of Clinical Oncology , which investigates the synergistic effects of perioperative electroacupuncture (EA) combined with flurbiprofen axetil (FA) on pain management and functional recovery following breast cancer surgery. In the study involving 130 patients, the EA group demonstrated a significant reduction in the incidence of moderate-to-severe movement-evoked pain and lower Visual Analog Scale scores at rest and during movement at 24 hours postoperatively compared to controls receiving sham acupuncture and FA. Enhanced recovery was further evidenced by superior scores in basic activities of daily living, including grooming, dressing, and transferring, alongside a notable decrease in postoperative complications such as nausea and vomiting. These findings underscore EA’s potential as a valuable, non-opioid adjunct within a multimodal analgesic regimen, contributing to improved early postoperative outcomes and aligning with enhanced recovery after surgery principles. While the study provides robust evidence for short-term synergistic analgesia, future research should aim to standardize EA protocols, elucidate its neurophysiological mechanisms, particularly its interaction with inflammatory pathways and central sensitization, and evaluate its long-term impact on patient-reported quality of life, chronic pain development, and overall oncological recovery trajectories.